Factors that contribute consumers adoption on online shopping : a case of Inno Travel & Tour Services Sdn. Bhd. / Xavier Francis - Francis, Xavier (2013)
Online shopping has been widely used by online marketers to distribute their product and service digitally to their customer, however it is hard for them to encourage and convince customer to make purchases from Internet. This research focuses on to identify the factors that can contribute consumers adoption on online shopping, which in regard to Inno Travel & Tour Services Sdn. Bhd., a tour agency company that based on Kota Kinabalu, Sabah. The main problem with online shopping is the cost that needs to be spent by the company to maintain the website preferences and in order to offer the best online shopping experience to the customer. Besides that, factors such as website layout, demographic, and customer resources are included as the main reason why customers adopt online shopping. As a result, Internet users that has been using Internet for a long time has higher tendency of adopting online shopping compared to those who did not, plus most online shopper are influence through social media such as Facebook and Twitter. Website layout considered as important part in a website, particularly for the sites that sells their product or service through Internet. A good website design can provide better interface which can make any website to be user friendly and easily navigated for the customer.